The Ability of Student’s Mathematical Representation in Contextual Problems Solving of Circle Material based on Mathematical Communication Ability - Mohamad Saiful Kowi; Iva Solihatun; Mutianah; Erna Fatmala; Fariz Apriyady; Neneng Aminah; Dede Endang Mascita (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Students in grade XI.11 of SMA Negeri 7 Cirebon City still have difficulty representing information into mathematical images and symbols on contextual problems, so it is important to understand their mathematical representation skills where this is influenced by one of the factors of students’ abilities, namely mathematical communication. This study aims to analyze the mathematical representation ability of students in solving mathematical contextual problems, especially in the inner circle and outer circle of triangles based on mathematical communication skills. The type of research is descriptive with a qualitative approach. The results of the study showed that: 1) the students with high mathematical communication skills were able to do well in symbolic and verbal representation. On visual representations, they are quite good although there are some mistakes in visualizing information; 2) the students with middle mathematical communication skills are quite good in symbolic representation. However, in visual and verbal representations, they are still lacking in visualizing information and expressing ideas or reasoning against material concepts; and 3) the students with low mathematical communication skills are quite good at symbolic representation even though there are shortcomings in writing formulas. In visual and verbal representations, they still have difficulty explaining ideas or ideas from information in contextual problems.